PRESERVICE CHEMISTRY TEACHERS’ CHEMICAL LITERACY BASED ON PISA AND TIMSS RESULTS FOR INTERNATIONAL AND INDONESIAN STUDENTS - Seprianto, Seprianto; Jofrishal, Jofrishal; Mauliza, Mauliza (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2017)
PISA and TIMSS results have been used as a basis for educational reform, but unfortunately, teachers’ understanding of PISA and TIMSS tests is rarely investigated. We evaluated 149 sophomore preservice chemistry teachers’ achievement in TIMSS and PISA-like test. As a way to reflect on TIMSS and PISA results, we compared preservice chemistry teachers’ achievement to PISA and TIMSS results for Indonesia and the international students. Results suggested that, to a certain degree, preservice chemistry teachers have a better chemical literacy than Indonesian students and a somewhat similar chemical literacy with international students.